Natural and anthrophic deteminants of distribution, structure and floristic composition of mangroves in the Natural Sanguaré Reserve, Colombia - Mira, Juan David (2019)
Mangroves have different degrees of interaction between oceanographic, climatic, geomorphological and soil conditions. Those interactions have strong impacts on local salinity conditions and availability of water and nutrients at local level, and on mangrove structure and composition. Based on the analysis of aerial photographs, field sampling and statistical multivariate analysis, floristic composition and structure of the mangroves present in the Sanguaré Natural Reserve were analyzed. Three types of forests were identified according to the physiographic classification of mangroves. A fridge mangrove dominated by Rhizophora mangle L. in a juvenile state, with low structural development, and two types of inland or basin mangroves dominated by Avicennia germinans (L.) L. The first of them, located behind the fridge mangrove, showed high salinity in the soil and in the interstitial water, predominance of sandy sediments, and low values of height and diameter at breast height (DBH) average of the trees. The second, with a low number of adult trees in all diameter categories, high basal area, low natural regeneration potential, and high concentrations of Fe and Cu in the soil, probably associated with contamination by domestic spills. The location of the first inner mangrove behind the fridge mangrove reveals the typical zonation of many mangroves in the world. The floristic composition, structure and distribution of the mangroves in the Sanguaré Reserve are the result of the interaction of local environmental variables such as salinity and soil texture, as well as the anthropic intervention prior to the establishment of the reserve and the current human presence being very close to the mangroves.